Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s12948-020-00122-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of 25-hydroxy vitamin D with asthma and its severity in children: a case–control study

Abstract: Background Universally, asthma has high prevalence rates and this has led numerous studies done into its causes. Despite extensive study on asthma the association between 25-Hydroxy Vitamin D (25(OH) vit. D) and asthma remains uncertain. In this study, the associations of 25(OH) vit. D levels with asthma and with the severity of asthma were evaluated. Methods This was a case–control study performed in 2015 in the city of Isfahan. In this study 520 children were studied. Children with asthma were classified as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 56 publications
3
4
0
1
Order By: Relevance
“…Diet was not considered in our study but may have been critical in maintaining vitamin D balance in this case. Various case-control studies have found differences in vitamin D levels between patients with asthma and healthy controls, particularly decreased vitamin D levels in a cohort of patients with asthma [51,52]. In the LT population, the mean 25(OH)D level was significantly elevated in the controls compared to the patients with BA group (p < 0.0001) and differed between the groups stratified by deficiency and sufficiency (p < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…Diet was not considered in our study but may have been critical in maintaining vitamin D balance in this case. Various case-control studies have found differences in vitamin D levels between patients with asthma and healthy controls, particularly decreased vitamin D levels in a cohort of patients with asthma [51,52]. In the LT population, the mean 25(OH)D level was significantly elevated in the controls compared to the patients with BA group (p < 0.0001) and differed between the groups stratified by deficiency and sufficiency (p < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…The level of vitamin D in the serum was not in associated with the severity of asthma in some studies [32]. However, there have also been reports of correlation between the vitamin D level and asthma severity in contrast [14,33].…”
Section: Is Vitamin D Deficiency Associated With Asthmamentioning
confidence: 90%
“…Vitamin D might play a role in asthma pathogenesis by affecting the development of the lungs, regulating the immune responses and remodeling of airway smooth muscle (ASM) [13]. The lower levels might be associated with severe forms and more severe manifestations [14].…”
Section: Introductionmentioning
confidence: 99%
“…The study design (case-control) that we followed to conduct this study remains like many others. This design was used in similar studies looking into the relationship between Vitamin D and asthma, conducted in Qatar, 5 USA, 10 Egypt, 11 Iran, 12 - 14 and India. 15 , 16 Age of both asthmatic (n = 87: cases) and non-asthmatic (n = 90: controls) ranged between 2 and 12 years, with a mean age of 6.05 ±2.05 in cases and 6.75±3.09 in controls which remains consistent to other studies in Iran, 12 , 14 India, 15 , 16 Turkey, 17 Israel, 18 USA, 10 and Bangladesh, 6 though we purposively excluded <2 years-old children since they reportedly suffer more from bronchiolitis as reported by Hassan et al 2 Bangladesh.…”
Section: Discussionmentioning
confidence: 99%